Nurses participating in Healthcare facility redesign: a qualitative descriptive study - Braid, Julia (Auckland University of Technology, 2010)
This study aims to reveal the experiences of senior nurses who have been expressly involved in healthcare facility and care redesign. This qualitative descriptive research describes the experiences of three senior nurses participating in hospital redesign at a New Zealand District Health Board (DHB). By examining their roles as project owners for facility and care redesign in project groups, we gain understanding of how such involvement currently exists, and what future recommendations might be formulated. Throughout New Zealand nurses have been involved in major hospital redevelopments, providing a unique opportunity to redesign facilities and systems of care. The participation of nurses in facility redesign projects contributes to a focus on the needs of key stakeholders, such as patient flow-through services, and reviewing current work practices and processes of care. Nurses demonstrate high levels of commitment to facility redesign projects holding key positions of representation. They seek to ensure integration with overall Ministry of Health strategic aims, service delivery requirements, client and population needs, and incorporating multidisciplinary healthcare concerns. Within this research paradigm the existing and apparent themes have been interpreted as Representation; Leadership; Relationships; and Creativity. These overarching themes were apparent in the data and thus provided important direction for the collation, presentation, and discussion of the related data and the findings. The subsequent recommendations focus on offering more support to enable senior nurses to be better equipped to fulfil this important role, with the aim being to ensure the new facility supports clients in a clinically safe environment.
Keywords: Nurses; Healthcare facility; Redesign; Participating; Experience; Qualitative